The harvest of the freshwater crayfish Astacus leptodactylus Eschscholtz in Turkey - Harlioglu, Muzaffer Mustafa (Springer, 2008)
This review focuses on the present distribution of populations of the crayfish Astacus leptodactylus that are harvested in Turkey. It also examines the history of this harvest and the impact that crayfish plague has had on them. Crayfish plague, caused by the fungus-like organism, Aphanomyces astaci Schikora, 1906, is a severe parasite of freshwater crayfish and has caused a lot of damage to A. leptodactylus populations in Turkey since 1984. Turkey was the largest provider of A. leptodactylus to Western Europe from 1970 (or possibly earlier) until 1986. For example, the peak production was reached in the early 1980s, with over 5,000 tonnes being exported in 1984. On the other hand, as a result of the crayfish plague the harvest of A. leptodactylus was reduced severely in most populations in Turkey after 1985. The harvest was only 320 tonnes in 1991. After the occurrence of crayfish plague in Turkey, in order to increase crayfish production uncontrolled A. leptodactylus stockings have been carried out in many waterbodies throughout Turkey. These introductions have caused an increase in the number of A. leptodactylus populations, but exploitation of A. leptodactylus is still under the pressure of the plague, although there has been a steady increase in crayfish production in recent years. The harvest increased to 2,317 tonnes in 2004. Fortunately, among those populations affected by crayfish plague, large amounts of A. leptodactylus can still be harvested from three lakes, Iznik (Bursa), Egirdir (Isparta) and Civril (Denizli). Thus, it seems that A. leptodactylus has a degree of resistance to crayfish plague. It is therefore interesting to investigate the resistance of A. leptodactylus caught from these populations to crayfish plague.
Keywords: Astacus leptodactylus; crayfish; distribution; harvest; plague; Turkey